On collective variables method in the microscopic theory of alloys - Gurskii, Z. (Condensed Matter Physics, 2000)
Ab initio approach is developed for thermodynamical investigations of disordered binary alloys. It is based on utilizing the collective variables method. The explicit expression for the free energy and the equation determining the alloy components' chemical potentials are obtained within the rigid lattice approximation and for the case when atomic static displacements (ASD) are taken into consideration. An ASD drastic effect on the behaviour of the binary correlation function Fourier components in the ﬁrst Brillouin zone is observed. The ASD is shown to favour the ordering tendency in alloys of Ca-Ba and K-Cs systems. An approach in which conﬁgurational and vibrational degrees of freedom are considered at the microscopic level in the grand partition sum calculation is advanced. The role of the atomic thermal vibrations in alloy forming is discussed. The condition when conﬁgurational and vibrational effects can be treated separately is formulated.